2014
DOI: 10.1111/risa.12290
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Variability and Uncertainty for Better Science and Decisions on Cancer Risks from Environmental Chemicals

Abstract: The National Research Council 2009 "Silver Book" panel report included a recommendation that the U.S. Environmental Protection Agency (EPA) should increase all of its chemical carcinogen (CC) potency estimates by ∼7-fold to adjust for a purported median-vs.-mean bias that I recently argued does not exist (Bogen KT. "Does EPA underestimate cancer risks by ignoring susceptibility differences?," Risk Analysis, 2014; 34(10):1780-1784). In this issue of the journal, my argument is critiqued for having flaws concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…38,39 Under this hypothesis, the implied J-shaped DR pattern for increased tumor risk would differ fundamentally from the linear-no-threshold DR pattern implied by the multistage somatic mutation (MSM) theory of tumorigenesis. 38 -43 Consistent with this hypothesis is evidence that potently anti-inflammatory synthetic oleanane triterpenes such as the acetylenic tricyclic bis -(cyano enone) TBE-31, 1-2-cyano-3-,12-dioxooleana-1,9(11)-dien-28-oyl (CDDO) ethyl amide (CDDO-EA), and CDDO-imidazole (CDDO-Im) activate the Nrf2-ARE cytoprotective pathway, induce phase II enzymes, and can suppress or completely block formation of enzyme-altered proliferative hepatocellular foci and liver tumors in rodents coadministered hepatotoxic liver carcinogens such as aflatoxin B 1 (also a potent mutagen) and carbon tetrachloride. 17,36,37,44,45 Although aflatoxin B 1 exposures induce macromolecular adducts with a linear DR pattern over a wide range of doses down to 0.16 ng/kg, coadministration of CDDO-Im before and during aflatoxin B 1 exposures that otherwise efficiently increase the occurrence of liver preneoplastic foci and tumors in male rats can nearly or completely eliminate these aflatoxin B 1 -induced lesions without proportionately reducing aflatoxin B 1 –DNA adducts, 36,34,37 which appears to be at odds with MSM theory.…”
Section: Discussionmentioning
confidence: 82%
“…38,39 Under this hypothesis, the implied J-shaped DR pattern for increased tumor risk would differ fundamentally from the linear-no-threshold DR pattern implied by the multistage somatic mutation (MSM) theory of tumorigenesis. 38 -43 Consistent with this hypothesis is evidence that potently anti-inflammatory synthetic oleanane triterpenes such as the acetylenic tricyclic bis -(cyano enone) TBE-31, 1-2-cyano-3-,12-dioxooleana-1,9(11)-dien-28-oyl (CDDO) ethyl amide (CDDO-EA), and CDDO-imidazole (CDDO-Im) activate the Nrf2-ARE cytoprotective pathway, induce phase II enzymes, and can suppress or completely block formation of enzyme-altered proliferative hepatocellular foci and liver tumors in rodents coadministered hepatotoxic liver carcinogens such as aflatoxin B 1 (also a potent mutagen) and carbon tetrachloride. 17,36,37,44,45 Although aflatoxin B 1 exposures induce macromolecular adducts with a linear DR pattern over a wide range of doses down to 0.16 ng/kg, coadministration of CDDO-Im before and during aflatoxin B 1 exposures that otherwise efficiently increase the occurrence of liver preneoplastic foci and tumors in male rats can nearly or completely eliminate these aflatoxin B 1 -induced lesions without proportionately reducing aflatoxin B 1 –DNA adducts, 36,34,37 which appears to be at odds with MSM theory.…”
Section: Discussionmentioning
confidence: 82%
“…However, regulatory-policy interest typically focuses not on a broad range of potency estimates for each chemical carcinogen, but rather on a conservatively defined upper confidence limit (UCL) on each such estimated potency. A recent comparison of UCLs on estimated human vs. rodent potencies for 24 chemical carcinogens showed that these UCLs exhibit a pattern consistent with the hypothesis that x = 0, and more specifically that UCL estimates of human and rodent potency for chemical carcinogens are, on average, equal to within a factor of <3 with 95% confidence (Bogen 2014).…”
Section: D2 Interspecies Extrapolation and Body-weight Adjustment Of Tumorigenic Potencymentioning
confidence: 72%
“…Linear-no-threshold (LNT) risk extrapolation has long been applied to estimate risks posed by low-level environmental (particularly by default for mutagenic) carcinogen exposures, based on the 60-year-old multistage somatic mutation/clonal expansion (MSM) theory of cancer. 1 First proposed and represented mathematically by Armitage and Doll in 1957, 2 the MSM theory overlaps most other current competing theories of cancer because the critical events it posits (namely, 2 or more critical oncogene mutations in a somatic stem cell, coupled if/as applicable with intrinsic and/or exposureinduced "promotion" by net proliferation of intermediate/premalignant cells) can also be induced or augmented by events posited as critical by those theories (eg, theories focusing on: 3 oxidative stress, infection, an inflammatory microenvironment, defective wound healing, chromosome damage, genomic instability, and epigenetic dysregulation). Generalizing MSM theory and Knudsen's related 2-mutation tumor suppressor inactivation model describing inherited susceptibility to retinobalstoma, [4][5][6] Moolgavkar, Venzon, Knudson (MVK) and colleagues represented the MSM model mathematically as a 2-stage doubly stochastic Poisson process (Figure 1, left) and fit this model well to many sets of experimental cancer bioassay and human cancer incidence data.…”
Section: Introductionmentioning
confidence: 99%